Upaya Meningkatkan Keterampilan Senam Lantai Guling Depan Menggunakan Media Bantu matras Bidang Miring Pada Siswa Kelas XI AKL 2 SMK N 6 Surakarta - Djoko Nugroho; Danang Eko Sutrisno; Iddo Christiana; Andi Karima; Andi Prasetyo; Dwi Wulansari; Rizki Raihan Syuhada; Sri Utami Wulandari (CV. ALIM'SPUBLISHING, 2024)
This research aims to find out whether the application of auxiliary media on an inclined plane mattress can improve the learning process and students' skills in learning floor exercise front rolls. The research method used to answer the research objectives was the class-room action research method. The subjects of this research were 33 students of class XI AKL 2 SMKN 6 Surakarta, consisting of 33 female students. The results of the pre-cycle research showed that the majority of students did not understand the front roll movement skill, so the pre-cycle scores were 42.42% (very good category), 15.15 (good category), 21.21 (fair category), 3 .03% (poor category) and 18.18% (very poor category. With an average student score of 7.0 (good category), and class learning completeness of 57.57% (low category). In the first cycle with learning through the application of incline mattress supporting media obtained a score from observations of student activities was 7 (good category), and the observation of teacher activities was also 7 (good category). The increase in students' skills in carrying out forward rolling skills is affected by the use of supporting media. Based on the results above, it can be concluded that the application of supporting media in learning has been proven to improve forward rolling skills.